First international external quality assessment scheme of nucleic acid amplification tests for the detection of Schistosoma and soil-transmitted helminths, including Strongyloides: A pilot study. - Piet Cools; Lisette van Lieshout; Rob Koelewijn; David Addiss; Sitara S R Ajjampur; Mio Ayana; Richard S Bradbury; Jason L Cantera; Daniel Dana; Kerstin Fischer; Rubina Imtiaz; Joyce Kabagenyi; et al. (Public Library of Science (PLoS), 2020)
Background Nucleic acid amplification tests (NAATs) are increasingly being used as diagnostic tools for soil-transmitted helminths (STHs; Ascaris lumbricoides, Trichuris trichiura, Necator americanus, Ancylostoma duodenale and A. ceylanicum), Strongyloides stercoralis and Schistosoma in human stool. Currently, there is a large diversity of NAATs being applied, but an external quality assessment scheme (EQAS) for these diagnostics is lacking. An EQAS involves a blinded process where test results reported by a laboratory are compared to those reported by reference or expert laboratories, allowing for an objective assessment of the diagnostic performance of a laboratory. In the current study, we piloted an international EQAS for these helminths (i) to investigate the feasibility of designing and delivering an EQAS; (ii) to assess the diagnostic performance of laboratories; and (iii) to gain insights into the different NAAT protocols used. Methods and principal findings A panel of twelve stool samples and eight DNA samples was validated by six expert laboratories for the presence of six helminths (Ascaris, Trichuris, N. americanus, Ancylostoma, Strongyloides and Schistosoma). Subsequently this panel was sent to 15 globally dispersed laboratories. We found a high degree of diversity among the different DNA extraction and NAAT protocols. Although most laboratories performed well, we could clearly identify the laboratories that were poorly performing. Conclusions/significance We showed the technical feasibility of an international EQAS for the NAAT of STHs, Strongyloides and Schistosoma. In addition, we documented that there are clear benefits for participating laboratories, as they can confirm and/or improve the diagnostic performance of their NAATs. Further research should aim to identify factors that explain poor performance of NAATs.